Indonesian health professions students’ perceptions toward an interprofessional education program: Findings after five years of implementation - Sari, Santi Purna; Soemantri, Diantha; Ayubi, Dian; Martha, Evi; Handiyani, Hanny; Findyartini, Ardi (Makara Journal of Health Research, 2020)
Background: The Interprofessional Education (IPE) program is important for preparing health professions students to provide future interprofessional collaborative practice. The Universitas Indonesia Health Sciences Cluster has been implementing the IPE program since 2013. A comprehensive evaluation is required following the implementation of the IPE program. The aim of the study was to evaluate the IPE course based on perceptions of undergraduate students at the Universitas Indonesia from 2013 to 2017. Methods: A mixed-methods study utilizing a semi-structured questionnaire was conducted with first year students following the completion of the first stage of the IPE course. A total of 2355 students (56.35%) from the 2013–2017 academic years completed the questionnaire. Results: The results showed that students’ perceptions of the IPE course improved each year on the domains of clear and relevant learning objectives, student-centered teaching methods, staff support, and supporting infrastructures. However, some room for improvement was identified, such as the need for tutors to have a more neutral attitude toward every student despite their background differences. Conclusion: The IPE course has been well perceived by students because of its comprehensive instructional design and principles of IPE that are implemented in the curriculum. The continuous cycles of improvement to maintain the quality of the IPE program will remain a challenge.